2015
DOI: 10.1515/bmc-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the first 17 amino acids of huntingtin in Huntington’s disease

Abstract: Huntington’s disease (HD) is caused by a polyglutamine (polyQ) domain that is expanded beyond a critical threshold near the N-terminus of the huningtin (htt) protein, directly leading to htt aggregation. While full-length htt is a large (on the order of ~350 kDa) protein, it is proteolyzed into a variety of N-terminal fragments that accumulate in oligomers, fibrils, and larger aggregates. It is clear that polyQ length is a key determinant of htt aggregation and toxicity. However, the flanking sequences around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 158 publications
(204 reference statements)
1
73
0
Order By: Relevance
“…In this study, a similar effect was observed upon coincubating it with NT 17 Q 35 P 10 K 2 peptide (Figure D–F), reaffirming its inhibitory property. This effect is due to the ability of Hum‐ NT 17 to form an amphipathic α‐helix with a strong hydrophobic core toward one side during its interaction with the NT 17 segment of NT 17 Q 35 P 10 K 2 . The Schiffer and Edmundson helical wheel representation, where the hydrophobic core of Hum‐ NT 17 was oriented exactly similar to that of the NT 17 segment of NT 17 Q 35 P 10 K 2 , might resemble this phenomenon (Figure ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, a similar effect was observed upon coincubating it with NT 17 Q 35 P 10 K 2 peptide (Figure D–F), reaffirming its inhibitory property. This effect is due to the ability of Hum‐ NT 17 to form an amphipathic α‐helix with a strong hydrophobic core toward one side during its interaction with the NT 17 segment of NT 17 Q 35 P 10 K 2 . The Schiffer and Edmundson helical wheel representation, where the hydrophobic core of Hum‐ NT 17 was oriented exactly similar to that of the NT 17 segment of NT 17 Q 35 P 10 K 2 , might resemble this phenomenon (Figure ).…”
Section: Resultsmentioning
confidence: 90%
“…This brings the polyGln chains closer in space, enhances its local concentration, and thus improves the efficiency of amyloid nucleation. Further monomer addition on to the postulated nuclei results in fibril‐elongation and amyloid‐rich aggregate formation …”
Section: Resultsmentioning
confidence: 99%
“…157, 220, 226, 227 Here, we will focus on PTMs that occur within the N17 domain of htt, as several of these impact polyQ structure and aggregation. 228 Several PTMs occur in this domain – i.e., phosphorylation, 229232 acetylation, 233 ubiquitination, 234 SUMOylation, 235, 236 palmitoylation, 237 oxidation, 238 and transglutamination. 239 Additionally, the initiator methionine of N17 can be proteolytically removed, and this may occur rapidly after or during synthesis.…”
Section: Post-translational Modifications Impact Aggregation and Toximentioning
confidence: 99%
“…[1] This, combined with the fact that this short N-terminal sequence harbors several residues that are subjected to diverse posttranslational modifications (PTMs), including phosphorylation, acetylation, ubiquitination and sumoylation (Scheme S1-A in the Supporting Information), suggests that PTMs may serve as reversible molecular switches for regulating Htt structure, interactome, cellular properties and toxicity. [2] However, the lack of knowledge about the enzymes involved in regulating these modifications has made it difficult to decipher their role in regulating the function(s) of Htt in health and disease.…”
Section: Main Textmentioning
confidence: 99%